Impulse Buying Behavior on Modern Retail - Nurcaya, I Nyoman; Rastini, Ni Made (Udayana Journal of Social Sciences and Humanities; Vol 2 No 2 (2018): UJoSSH, September 2018DO - 10.24843/UJoSSH.2018.v02.i02.p06, 2018)
Retail business has a rapid development, especially in Indonesia. It is indicated by the increasing number of traditional retail business which begins to fix itself into a modern retail business or an independent modern retail business. The increased number of modern retail pushes the competition of the business world to the next level, so it requires retail entrepreneurs to optimize their strategy which known as marketing mix retail. Impulse Buying Behavior as a result of the successful strategic marketing mix retail often wished to happen to indicate the existence of the retail business. Similarly, with the modern retail which exists in Denpasar city, who is trying to develop its marketing mix strategy in the hope of impulse buying behavior. This research has a purpose of explaining the influence of Merchandise , Atmospheric outlet and promotion toward Impulse Buying Behavior with positive emotion variable as an Intervening variable on modern retail in Denpasar city. To reach that purpose, 100 (one hundred) respondents are used which selected by purposive sampling with a questionnaire as the method for data gathering. The data is processed with the SEM PLS analysis tool. The result shows that Merchandise variable, Atmospheric outlet , and promotion has a positive influence significantly on Positive emotion. The same with Merchandise variable, Atmospheric outlet and Promotion, and positive Emotion significantly influence the Impulse buying behavior .  Positive Emotion variable significantly partially mediates the influence of Merchandise , Atmospheric outlet , and Promotion about Impulse buying behavior .